ANALISIS KINERJA SENSOR TEMPERATUR TERHADAP SUHU PERMUKAAN KACA PADA SISTEM PEMANAS KACA (WINDOWS ANTI ICE SYSTEM) RUANG KEMUDI (COCKPIT) PESAWAT B 737-800 - purnomo, Bayu; Pratama2, Ilham; Purnomo, Joko (University of Muhammadiyah Tangerang, 2024)
One of the conditions faced by airplanes when moving through the air is the very cold surrounding air temperature. If the altitude increases, the air temperature will decrease, from around 17℃ to -52℃. For every 100 meter increase in height the temperature decreases by 0.61oC.To prevent the occurrence of ice lumps on the surface of the aircraft due to the surrounding air temperature reaching -520 C which can cause interference and endanger flight safety, certain parts of the aircraft surface are equipped with a heating system (anti-ice system) to melt the ice lumps into liquid. one of which is installed on the glass of the aircraft steering room (cockpit) which is usually called the windows anti-ice system. Several reports of incidents involving the cockpit glass heating system experiencing problems were caused by sensors that were not working normally. This research aims to determine the performance of the sensor regarding changes in the temperature of the cockpit glass using the method of measuring the sensor resistance value and the temperature of the cockpit glass. It is hoped that the results of this research can be used as material for further research to determine the reliability of the sensors installed in the cockpit glass from analysis of data on changes in resistance values to temperature and sensor age since the glass was installed on the aircraft. So it can be predicted when the B737-800 cockpit glass must be replaced before damage occurs during aircraft operation.